Visual Analysis of the Tempo Magazine Cover Edition 4542 16- 22 September 2019 using the Semiotic Method - Iskandar, M S; Zhafran, B (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was to show the cover that criticizes using the illustration on the cover of the TEMPO magazine 4542 edition (16-22 September 2019) entitled "Promises Stay Promises" reap polemic in the community because it displays illustrations Jokowi with a shadow who has a long nose. The cover is reported to the Council Press by Jokowi Mania Volunteers, Emanuel Ebenezer as the head of Jokowi’s Volunteers said that the media cannot take sides and the cover violates the journalistic code of ethics. This research focuses on reviewing the meaning of the visuals published on the cover of Tempo Magazine 4542 edition 16-22 September 2019 using the semiotic analysis method with qualitative approach in order to discover Signs Based on Visual Elements (Image) and Signs Based on Typographic Elements (Text) that nose is a subtle insinuation from Tempo Magazine to the Jokowi government, which has broken its promise of strengthening the KPK and its anticorruption behaviors. This study aims to determine the existing messages and meanings. In the study it can be concluded that the long nose used by magazines Tempo refers to the character Pinocchio, from Italian folklore.